High-average-power and high-pulse-energy CEP-stable few-cycle pulses: Status of the ELI-ALPS HR2 laser system - Haedrich, Steffen; Shestaev, Evgeny; Walther, Nico; Nagy, Tamas; Simon, Peter; Blumenstein, Andreas; Klenke, Arno; Klas, Robert; Buldt, Joachim; Stark, Henning; Gebhardt, Martin; Breitkopf, Sven; et al. (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Few-cycle laser systems providing both high repetition rates and high pulse energies are a major focus of next-generation light sources. Consequently, the research facility of the Extreme Light Infrastructure (ELI) that is devoted to the generation of isolated attoseconds pulses, (ELI-ALPS in Szeged, Hungary), has set the demand for a laser system delivering carrier-envelope phase (CEP) stable pulses with 5 mJ of pulse energy, 6 fs pulse duration at 100 kHz repetition rate, which corresponds to an average power of 500 W [1]. This laser system, that is named HR2 (the high-repetition-rate beam line), is currently under development at Active Fiber System GmbH. Achieving these ambitious laser parameters is done by merging the robust techniques of coherent combination as an average-power scaling concept and the use of stretched hollow-core fiber technology for nonlinear pulse compression [2].
CRIS-Team Scopus Importer:2023-04-20